Characterization of Sleep in Aplysia californica - Vorster, Albrecht P.A. (Associated Professional Sleep Societies, LLC, 2014)
STUDY OBJECTIVE: To characterize sleep in the marine mollusk, Aplysia californica. DESIGN: Animal behavior and activity were assessed using video recordings to measure activity, resting posture, resting place preference, and behavior after rest deprivation. Latencies for behavioral responses were measured for appetitive and aversive stimuli for animals in the wake and rest states. SETTING: Circadian research laboratory for Aplysia. PATIENTS OR PARTICIPANTS: A. californica from the Pacific Ocean. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: Aplysia rest almost exclusively during the night in a semi-contracted body position with preferential resting locations in the upper corners of their tank. Resting animals demonstrate longer latencies in head orientation and biting in response to a seaweed stimulus and less frequent escape response steps following an aversive salt stimulus applied to the tail compared to awake animals at the same time point. Aplysia exhibit rebound rest the day following rest deprivation during the night, but not after similar handling stimulation during the day. CONCLUSIONS: Resting behavior in Aplysia fulfills all invertebrate characteristics of sleep including: (1) a specific sleep body posture, (2) preferred resting location, (3) reversible behavioral quiescence, (4) elevated arousal thresholds for sensory stimuli during sleep, and (5) compensatory sleep rebound after sleep deprivation. CITATION: Vorster AP, Krishnan HC, Cirelli C, Lyons LC. Characterization of sleep in Aplysia californica. SLEEP 2014;37(9):1453-1463.